2016
DOI: 10.1080/15548627.2016.1196316
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inSaccharomyces cerevisiaerequires the monomeric GTP-binding proteins, Arl1 and Ypt6

Abstract: Macroautophagy/autophagy is a cellular degradation process that sequesters organelles or proteins into a double-membrane structure called the phagophore; this transient compartment matures into an autophagosome, which then fuses with the lysosome or vacuole to allow hydrolysis of the cargo. Factors that control membrane traffic are also essential for each step of autophagy. Here we demonstrate that 2 monomeric GTP-binding proteins in Saccharomyces cerevisiae, Arl1 and Ypt6, which belong to the Arf/Arl/Sar prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 74 publications
2
40
1
Order By: Relevance
“…Together, these results further support the notion that Arl1 activation at the Golgi exerts distinct biological activities, which may be involved in regulating the Cvt pathway. Although it has been shown that the Cvt pathway may be affected by dysfunction of Arl1 at non‐permissive temperature, in our study, arl1 Δ cells only exhibited a minor defect in Ape1 processing. Interestingly, this defect was strengthened by Cog8 malfunction.…”
Section: Discussioncontrasting
confidence: 78%
“…Together, these results further support the notion that Arl1 activation at the Golgi exerts distinct biological activities, which may be involved in regulating the Cvt pathway. Although it has been shown that the Cvt pathway may be affected by dysfunction of Arl1 at non‐permissive temperature, in our study, arl1 Δ cells only exhibited a minor defect in Ape1 processing. Interestingly, this defect was strengthened by Cog8 malfunction.…”
Section: Discussioncontrasting
confidence: 78%
“…Similarly, in ypt6 Δ cells, Snc1 traffic toward the Golgi was negatively affected ( Siniossoglou et al, ; Liu et al, ). It is clear that Ypt6 functions as a GTPase to facilitate endosome‐to‐Golgi retrograde transport as well as autophagy (Siniossoglou et al, ; Luo and Gallwitz, ; Yang and Rosenwald, ). Codeletion of VPS1 and YPT6 genes led to synthetic lethality (Figure ), suggesting the possibility of a functional link between Vps1 and Ypt6.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to acting as a transport regulator between endosomes and the Golgi, yeast Arl1 − together with the Rab GTPase Ypt6 − is required for starvation-induced autophagy under high-temperature stress (Yang and Rosenwald, 2016). Interestingly, a novel role of Arl1 in regulation of fungal morphogenesis and virulence has recently been revealed in a Candida-albicans-infected oropharyngeal candidiasis mouse model (Labbaoui et al, 2017).…”
Section: Yeastmentioning
confidence: 99%
“…In mammalian cells, these functions affect a wide range of fundamental cellular processes, including cell polarity (Lock et al, 2005), innate immunity (Bremond et al, 2009;Lieu et al, 2008;Murray and Stow, 2014;Stanley et al, 2012), lipid droplet and chylomicron formation (Hesse et al, 2013;Jaschke et al, 2012), as well as the secretion of insulin (Gehart et al, 2012), chromogranin A (CruzGarcia et al, 2013) and matrix metalloproteinases (MMPs) (Eiseler et al, 2016). In yeast, Arl1 and its effectors are also involved in numerous functions, such as maintenance of cell wall integrity (Liu et al, 2006), ion homeostasis (Marešová and Sychrová, 2010;Munson et al, 2004;Rosenwald et al, 2002), tolerance to stress factors (Jaime et al, 2012;Marešova et al, 2012;Yang and Rosenwald, 2016), regulation of cell proliferation (Benjamin et al, 2011), the unfolded protein response (UPR) (Hsu et al, 2016) and also in the ability of yeast to cause disease (Labbaoui et al, 2017). In addition, these factors regulate the quality control of the endoplasmic reticulum (ER) (Lee et al, 2011), tissue development (Eisman et al, 2006;Torres et al, 2014) and neuronal growth in Drosophila (Chang et al, 2015), and control cell viability in parasites (Price et al, 2005).…”
Section: The Physiological Roles Of Arl1mentioning
confidence: 99%
See 1 more Smart Citation